Book review: Debojyoti Das. 2018. The Politics of Swidden Farming: Environment and Development in Eastern India. (August 2021) - Padel, Felix
Debojyoti Das. 2018. The Politics of Swidden Farming: Environment and Development in Eastern India . Anthem Press, 252 pages, Price £70 (£18.36 kindle).